The influence of sulfathiazole on the macroalgae Ulva lactuca - Leston, Sara (2014)
Sulfonamides (SA) are a class of antibiotics routinely found in environmental matrices and therefore their role as contaminants should be investigated in non-target organisms. With this purpose the present experimental work has evaluated the exposure of the chlorophycean Ulva lactuca L. to sulfathiazole (STZ), a SA drug commonly used in aquaculture, at two concentrations representing prophylactic (25 lgmL 1) and therapeutic (50 lgmL 1) administrations. Results showed that STZ exhibits high stability in seawater with only 18% degradation over the 5 d assay at both dosages tested. Also, macroalgae demonstrated an efficient uptake capacity with constant internal concentrations after 24 h regardless of the external solutions and thus should be considered as a bioindicator species in risk assessment. Both STZ concentrations induced a slight inhibition of the macroalgae growth after 96 h.